PENGARUH KOMUNIKASI DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA PEGAWAI RUTAN KLAS IIB RANGKASBITUNG - Hilman Hilmawan; Yumhi Yumhi (Universitas La Tansa Mashiro, 2019)
The purpose of this study is to determine whether the variables of communication and transformational leadership alone - or jointly - can have an effect on the satisfaction of Employees in the House Detainee Class IIB Rangkasbitung and to know which variable is the most dominant influence employee job satisfaction at Home Prisoner of Class IIB Countries Rangkasbitung. The total population is 52 people and the number of samples of 50 employees Rutan Klas IIB Rangkasbitung taken at random. data method used is by using the technique of interview and also spread the questionnaire with job satisfaction variable 6 Statement, Communication 6 statement, transformational leadership 6 statement. Data analysis used is Test of Normality and multiple linear regression. The hypothetical test is performed by T Test for its own self-effect and F-Test for stimulant or joint effect treated using SPSS.The result of the research shows that transformational communication and leadership have an effect on job satisfaction of Rutan Klas IIB employee Rangkasbitung, and Transformational Leadership has a dominant influence on Job Satisfaction.